Women’s psychological experiences of preterm labour and birth which results in an intrapartum stillbirth or a neonatal death: an empty systematic review - Semra Worrall; Elana Payne; Elana Payne; Rebecca E. Fellows; Rebecca E. Fellows; Olivia Pike; Naomi H. Carlisle; Jenny Carter; Anja Wittkowski; Karen Burgess; Karen Burgess; Claire Storey; et al. (Frontiers in Psychiatry)
IntroductionNearly three quarters of stillbirths and neonatal deaths occur in infants born prematurely. The mothers of these children may be at increased risk of developing mental health difficulties as a result of their premature labour and/or subsequent loss.MethodsThis systematic review was conducted to understand the psychological experiences of mothers who gave birth prematurely to a baby who subsequently dies as a result of an intrapartum stillbirth or a neonatal death. Ten databases were searched. Any studies which included women who had suffered a perinatal bereavement as a result of preterm labour and birth, in any country, and in any language were eligible to be included. Studies focusing on antepartum stillbirth or in utero death were excluded due to not having the element of preterm labour and/or birth within the studies. Risk of bias was to be assessed using the Critical Appraisal Skills Programme.ResultsFollowing the screening of citations, no studies were eligible for inclusion in the review. The majority of studies were excluded due to a lack of distinction in terms of intrapartum or antepartum stillbirth, or grouping of types of perinatal loss. Had the inclusion criteria been less stringent and the three most common reasons for exclusion been removed, 19 studies would have been eligible for inclusion in the review, and we present a brief summary of these findings.DiscussionThese review findings highlight the need for more research into the psychological experiences of mothers of preterm infants whose baby subsequently dies, whereby future studies should consider routine reporting of gestational age. To address the identified gaps, future research should consider alternative methods or broader inclusion criteria to capture relevant data. Emphasising the importance of reporting gestational age and distinguishing between types of perinatal loss will enhance the specificity of research findings.